Nature: A Notable Feature of Robert Frost’s poetry - Shrestha, Muna (Journal of Advanced Academic Research, 2020)
The aim of this present article is to examine Robert Frost’s poetical theme and its values which explain the voice of Nature and also to highlight the treatment of Nature in some of his selected Poems. Frost is a famous American Poet and his poems are mostly autobiographical in subject. During this period, when modern poetry is becoming more complex, Frost gets success using his poetic style with refined and simple language. He has been mostly influenced by the environment around him while composing his masterpieces. He uses different phrases and thrill in poetry. His central theme doesn’t concentrate on the typical rural life but on the dramatic conflict happening in the natural world. He expresses deep love and sympathy towards Nature and utilizes it to express his viewpoint and to make his verse fascinating. He thinks Nature is not only the source of pleasure, but also an inspiration for human wisdom. His poems contain symbolism, hidden meanings, sounds, rhyme, meter, metaphors and more.